s.t. (Mexico : Fuera de Registro, 2000)
Projekt : affiches tijdens de verkiezingen (op 2 juli 2000) in Mexico stad.
Spaans
boek
Keywords: Barrera, Eduardo; Beltrán, Erick; Madrid, Ana Bertha; Magallanes, Alejandro; Montes de Oca, Héctor; Prado, Claudia; Rodriguez Romo, Sebastián; Sagahón, Leonel; Volpi, Mauricio; Mexico